ANALISIS PEMASARAN DAN PENDAPATAN USAHATANI SEMANGKA KELOMPOK TANI RIDHO LESTARI DI DESA TEMBOKREJO KECAMATAN MUNCAR KABUPATEN BANYUWANGI - Binta Islami Amnimarlianda; Imam Syafi'i; Agus Supriono (University of Jember, 2018)
Banyuwangi Regency is one of the centers of watermelon production in East Java Province. Muncar Sub-district is a watermelon producing district with the highest harvest and production area in Banyuwangi. The village of Muncar sub-district known as watermelon producing village is Tembokrejo Village. This research conducted in the Tembokrejo Village at the farmer group of Ridho Lestari has three purposes, namely: (1) to know the marketing channel of watermelon, (2) to know the margin and efficiency of watermelon marketing, and (3) to know the income and efficiency of watermelon farming. The results showed that farmers of watermelon farmer group Ridho Lestari have 4 marketing channels, namely: (a) farmers - wholesalers - retailers - consumers, (b) farmers - middlemen - wholesalers - retailers - consumers, (c) farmers - middlemen - retailers - consumers, and (d) farmers - exporters - importers; (2) the non-exported watermelon marketing margin is low and efficient, while the export marketing margin is high and inefficient; (3) Ridho Lestari farmers' watermelon farmer's income is beneficial and the cost of watermelon farming is efficient.